A low-field electron mobility analysis of cubic boron nitride. (1st September 2022) - Chilleri, John; Wang, Yana; Shur, Michael S.; O'Leary, Stephen K.
Abstract: We examine zinc-blende boron nitride's low-field electron transport response. In particular, within the framework of a relaxation-time approximation analysis, we probe how the individual scattering processes contribute to the total electron drift mobility. The scattering processes considered include the ionized impurity, polar optical phonon, acoustic deformation potential, piezoelectric, and inter-valley scattering processes. A comparison with the results of experiment is presented. Highlights: We examine zinc-blende boron nitride's low-field electron transport response. How the individual scattering processes contribute to the total low-field electron drift mobility associated with this material is probed. A comparison with the results of experiment is provided. A new approach to characterizing the importance of the various scattering mechanisms is introduced as a corollary to this analysis.